The taxation policy effect of the EU's states members on their investments. A quantitative investigation of the matter - Παπακωνσταντίνου, Ευάγγελος (SPOUDAI Journal of Economics and Business, 2007)
In today’s opened and globalized economy, the existence of economic competition, becomes more complex and more difficult even for economies that had long tradition in issues of economic development and economic competition, as those of Europe and the USA etc. The present study emerges to investigate how the implementation of financial policy can influence, and to what degree, the level of investments in the countries members of the European Union. Considering that the economic development and prosperity are based to a large extent on the investments of capitals in a country, we hope that the findings of the present study will add more value to the effort for the solution of the problem by the countries of Europe.